Using sensitivity analysis to construct a model for measuring sustainable development according to the Bellagio principles - Mayekiso, Luthando (My University, 2012)
The study investigates models and processes that could be used by decision-makers to influence policy. The objectives of the study are to illustrate the considerations in the use of information systems and modeling in the context of sustainable development in South Africa. The problem considered is that of measuring South Africa‟s progress toward sustainable development. The study is conducted at a national level. The design uses statistical indicators arranged into a model based information system using the Bellagio principles of 1996. The statistical indicators are assembled from the United Nations 1993 System of National Accounts, UN 1995 Driver-Pressure-State-Impact-Response framework, United Nations 2003 System of integrated Environmental and Economic Accounting, Basel Committee‟s 2004 Basel II framework, and South African Presidency 2010 Developmental indicators frameworks. The South African economy is conceptualised as a dynamic system composed of five types of capital. The fitted model is a vector autoregressive time series model of order p on a set of statistical factors that describe the South African economy. The robustness of the model to assumptions is evaluated using sensitivity and uncertainty analysis. The optimality of the model output for decision making is evaluated using decision theory. The study will facilitate an evidence based approach to managing South Africa‟s progress towards sustainable development.
MSc., Faculty of Science, University of the Witwatersrand, 2011
Keywords: Sensitivity theory (mathematics), statistical methods; Sensitivity theory (mathematics)